Tunelamento ressonante de férmions massivos de Dirac em sistemas de simples e dupla barreiras em monocamada de grafeno - Teixeira, José Dilson da Silva (2015)
Nowadays, several efforts have been made by research groups around the physical properties of the graphene in view of the possible technological applications of their unique structural and electronic properties. The graphene comes as a fort candidate to substitute the inorganic semiconductors. Initially in this work, we made a description of the graphene crystal structure to elucidate its nature. The electronic properties of this material are attractive due to several analogies between the transport phenomena and other phenomena studied by quantum electrodynamic as, for instance, Klein tunneling. From the point of view of the tight-binding approximation, we obtained the dispersion relation and the structure of the energy bands of the graphene, thus outlining its electronic spectrum. Also,we indicated some curious results that demonstrate the atypical nature of this material. The main objective of this study was to analyze the behavior of the charge carriers by the transfer matrix technique to obtain the numerical solution of transmissivity, conductance and tunneling current density in the graphene. The transmissividade was analyzed as function of the incident energy and of the angle of incidence for systems with single and double potential barriers, emphasizing the effect of the variation of the gap of energy. We also verified quantum oscillations due to Fabry -Pérot interference and Klein tunneling - an unique property in the graphene. The insertion of the energy gap generated the gap in the transmissivity curve, as well as resonant peaks that become more sharper with the increment of that gap. From the transmissivity results, we enlarged our understanding of the electronic properties in relation to conductance and current density in the graphene. Such properties are shown quite favorable the production of nanoelectronic devices of high performance..